Metode Dialog Interaktif sebagai Strategi Pembelajaran Al-Qur’an Hadits dalam Meningkatkan Kesadaran Akhlak: Studi Refleksi Hadits tentang Menjaga Diri dari Api Neraka - Ilma, Labibah Sayaka; Suyudi, M. (DIMAR: Jurnal Pendidikan Islam, 2025)
This study aims to analyze the implementation of the interactive dialogue method in Islamic education as a strategy to enhance students’ moral awareness. The focus is centered on the reflection and understanding of the hadith "Save yourselves from the fire of hell", which emphasizes individual responsibility in moral and spiritual development. The research employs a literature review method, examining a range of scholarly sources that explore both the theoretical and practical aspects of interactive dialogue in the context of Islamic educational practices. The concept of interactive dialogue is explored as a means to create a dynamic and participatory learning environment, where students are encouraged to think critically, ask questions, and reflect on their values and behavior in light of Islamic teachings. Findings from the literature reveal that this method is highly effective in helping students gain a deeper comprehension of religious texts, especially hadith, by relating them to real-life moral challenges. Techniques such as open-ended discussions, contextual case studies, and guided self-reflection activities contribute to more meaningful learning experiences. These approaches not only enhance students’ cognitive engagement but also promote the internalization of Islamic values, encouraging the formation of strong moral character. In conclusion, the interactive dialogue method serves as a valuable educational tool that supports both intellectual and ethical development, making Islamic teachings more relevant and impactful in students’ everyday lives.